2008
DOI: 10.1017/s0003598x00096447
|View full text |Cite
|
Sign up to set email alerts
|

From Sicily to Salcombe: a Mediterranean Bronze Age object from British coastal waters

Abstract: Bronze Age objects found in the English Channel off Salcombe, southern Britain, include an implement which has its normal home in Sicilian agriculture -perhaps as a plough shoe. The authors assemble and classify the objects and consider the web of exchange networks that brought the artefact from Sicily to Devon via France around the thirteenth century BC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 14 publications
0
5
0
1
Order By: Relevance
“…There are a few archaeological finds that suggest some exchange between southern Britain and the Mediterranean as early as the thirteenth century BC. Along with the weights, the site of Salcombe has also yielded a Sicilian strumento con immanicatura a cannone —perhaps a plough shoe (Needham & Giardino 2008; Needham et al 2013: 85–86). Such a device has hitherto only been found in thirteenth- to eighth-century BC contexts in Sicily (Giardino 1995: 17–26, 291–92).…”
Section: Discussionmentioning
confidence: 99%
“…There are a few archaeological finds that suggest some exchange between southern Britain and the Mediterranean as early as the thirteenth century BC. Along with the weights, the site of Salcombe has also yielded a Sicilian strumento con immanicatura a cannone —perhaps a plough shoe (Needham & Giardino 2008; Needham et al 2013: 85–86). Such a device has hitherto only been found in thirteenth- to eighth-century BC contexts in Sicily (Giardino 1995: 17–26, 291–92).…”
Section: Discussionmentioning
confidence: 99%
“…They recovered 31 objects including bronze objects of 22 weapons/fragments, one palstave-adze, one cauldron handle, one rectangular block/weight, one Sicilian strumento con immanicatura a cannone, three gold objects/fragments, an iron awl with a bone handle and a tin lump (Needham et al, 2013). In the absence of surviving organic material suitable for radiocarbon dating, detailed typo-chronological analyses of diagnostic bronze and gold objects, supported by radiocarbon dates from terrestrial sites containing comparable metalwork, placed the Salcombe assemblage in the Middle Bronze Age Penard metalwork phase (c. 1300-1150 BC) with the exception of one Type Nantes bronze sword which typologically dated to the Late Bronze Age Ewart Park metalwork phase (c. 1000-800 BC) (Needham and Giardino, 2008;Needham et al, 2013;Brandherm and Moskal-del Hoyo, 2014). Compositional analysis revealed that the bronzes were consistent with this dating as well as a high level of purity in the tin lump (Northover, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…These groups often enrich archaeology, not only with the, often speculator, results that they can produce (e.g. Needham and Giardino 2008), but also with the wide skills base that they bring with them from their professional lives. With limited time to spend on archaeology, they often, not unreasonably, value training less against time spent on site.…”
Section: Education For Practitioners Beyond Universitymentioning
confidence: 99%